Human responses to Middle Holocene climate change on California's Channel Islands - Kennett, D. J.; Kennettb, J. P.; Erlandson, J. M.; Cannariato, K. G. (Quaternary Science Reviews, 2007)
High-resolution archaeological and paleoenvironmental records from California's Channel Islands provide a unique opportunity to examine potential relationships between climatically induced environmental changes and prehistoric human behavioral responses. Available climate records in western North America (7-3.8 ka) indicate a severe dry interval between 6.3 and 4.8 ka embedded within a generally warm and dry Middle Holocene. Very dry conditions in western North America between 6.3 and 4.8 ka correlate with cold to moderate sea-surface temperatures (SST) along the southern California Coast evident in Ocean Drilling Program (ODP) Core 893A/B (Santa Barbara Basin). An episode of inferred high marine productivity between 6.3 and 5.8 ka corresponds with the coldest estimated SSTs of the Middle Holocene, otherwise marked by warm/low productivity marine conditions (7.5-3.8 ka). The impact of this severe aridity on humans was different between the northern and southern Channel Islands, apparently related to degree of island isolation, size and productivity of islands relative to population, fresh water availability, and on-going social relationships between island and continental populations. Northern Channel Islanders seem to have been largely unaffected by this severe and phase. In contrast, cultural changes on the southern Channel Islands were likely influenced by the climatically induced environmental changes. We suggest that productive marine conditions coupled with a dry terrestrial climate between 6.3 and 5.8 ka stimulated early village development and intensified fishing on the more remote southern islands. Contact with people on the adjacent southern California Coast increased during this time with increased participation in a down-the-line trade network extending into the western Great Basin and central Oregon. Genetic similarities between Middle Holocene burial populations on the southern Channel Islands and modern California Uto-Aztecan populations suggest Middle Holocene movement of people at this time from southern California desert environs westward to the southern islands, a migration perhaps stimulated by increased continental aridity. (c) 2006 Elsevier Ltd. All rights reserved.
158ghTimes Cited:49Cited References Count:167

Early Holocene land use and subsistence on eastern Santa Rosa Island, California - Rick, T. C.; Kennett, D. J.; Erlandson, J. M. (Current Research in the Pleistocene, 2006)
id: 1021

Intra-shell radiocarbon variability in marine mollusks - Culleton, B. J.; Kennett, D. J.; Ingram, B. L.; Erlandson, J. M.; Southon, J. (Radiocarbon, 2006)
id: 1019

A geoarchaeological chronology of Holocene dune building on San Miguel Island, California - Erlandson, J. M.; Rick, T. C.; Peterson, C. (Holocene, 2005)
A data base of 114 C-14 dates from 40 archaeological sites in San Miguel Island sand dunes provides a general chronology for Holocene dune building. Although rising seas have probably submerged earlier evidence, postglacial dune building on San Miguel began as early as 10 000 years ago. More intensive dune building dates to the middle and late Holocene, including large parabolic dunes that traverse the island and climb some of the highest landforms. Native American peoples lived on and altered island sand dunes for nearly 10 000 years, and native burning and other landscape alterations may have contributed to periodic destabilization of island dunefields. Accumulation of cultural debris also facilitated anthropogenic soil formation in many coastal localities, however, and over the millennia midden debris protected large expanses of the island's coastal perimeter from wind erosion. With the introduction of sheep c. AD 1850, destabilization and erosion of dune soils caused by overgrazing and other human impacts reached unprecedented levels, devastating the island's natural ecology. In recent decades, with the removal of sheep and other exotic animals from the island, the dunes have begun to restabilize.
992ziTimes Cited:23Cited References Count:31

Preliminary report on the archaeology and paleoecology of the Abalone Rocks Estuary, Santa Rosa Island, California - Rick, T. C.; Kennett, D. J.; Erlandson, J. M. (Proceedings of the Sixth California Islands Symposium, 2005)
id: 468

Radiocarbon dating and the "old shell" problem: direct dating of artifacts and cultural chronologies in coastal and other aquatic regions - Rick, T. C.; Vellanoweth, R. L.; Erlandson, J. M. (Journal of Archaeological Science, 2005)
Archaeologists have long recognized the problem of the "old wood" effect in radiocarbon dating charcoal and wood samples, the age of which may be hundreds of years older than their use by humans. Such problems have resulted in significant changes in how most researchers select wood and charcoal samples for C-14 dating, with many now using relatively short-lived carbonized materials for dating. Despite the significant strides made in our understanding of the potential biases of the "old wood" effect, little emphasis has been placed on the possible impacts of dating "old shell" in archaeological deposits. The use of marine shell for C-14 dating is widespread in coastal areas around the world, including a growing emphasis on the dating of individual shell artifacts via Accelerator Mass Spectrometry (AMS). In dating shell artifacts, we have obtained several dates older than associated C-14 dates for short-lived subsistence remains from the same deposits, including great disparities (> 10,000 years) and more subtle differences (>= 100 years). These discrepancies appear to be due to the use of old shells by humans to make beads and other artifacts, including shells collected from fossil deposits, older archaeological sites, and beaches. The problems caused by the use of old shells to make beads and other artifacts are surmountable through careful sample selection, analysis of multiple 14 C dates on a variety of materials, and proper calibration procedures. (c) 2005 Elsevier Ltd. All rights reserved.
970xgTimes Cited:33Cited References Count:40

Dates, demography, and disease: Cultural contacts and possible evidence for old world epidemics among the island Chumash - Erlandson, J. M.; Rick, T. C.; Kennett, D. J.; Walker, P. L. (Pacific Coast Archaeological Society Quarterly, 2003)
id: 1022

Emergence of Late Holocene sociopolitical complexity on Santa Rosa and San Miquel Islands - Kennett, D. J.; Conlee, C. A. (Catalist to Complexity: The Late Holocene Archaeology of the California Coast: Perspectives in California Archaeology, 2003)
id: 472

On the antiquity of the single-piece shell fishhook: AMS radiocarbon evidence from the southern California coast - Rick, T. C.; Vellanoweth, R. L.; Erlandson, J. M.; Kennett, D. J. (Journal of Archaeological Sciences, 2002)
id: 1024